Xenomicrobiology: a roadmap for genetic code engineering. Issue 5 (4th August 2016) - Acevedo‐Rocha, Carlos G.; Budisa, Nediljko
Summary: Biology is an analytical and informational science that is becoming increasingly dependent on chemical synthesis. One example is the high‐throughput and low‐cost synthesis of DNA, which is a foundation for the research field of synthetic biology (SB). The aim of SB is to provide biotechnological solutions to health, energy and environmental issues as well as unsustainable manufacturing processes in the frame of naturally existing chemical building blocks. Xenobiology (XB) goes a step further by implementing non‐natural building blocks in living cells. In this context, genetic code engineering respectively enables the re‐design of genes/genomes and proteins/proteomes with non‐canonical nucleic (XNAs) and amino (ncAAs) acids. Besides studying information flow and evolutionary innovation in living systems, XB allows the development of new‐to‐nature therapeutic proteins/peptides, new biocatalysts for potential applications in synthetic organic chemistry and biocontainment strategies for enhanced biosafety. In this perspective, we provide a brief history and evolution of the genetic code in the context of XB. We then discuss the latest efforts and challenges ahead for engineering the genetic code with focus on substitutions and additions of ncAAs as well as standard amino acid reductions. Finally, we present a roadmap for the directed evolution of artificial microbes for emancipating rare sense codons that could be used to introduce novel building blocks. The development of such xenomicroorganisms endowed with a 'genetic firewall' will also allow to study and understand the relation between code evolution and horizontal gene transfer. Abstract : Virtually universal on earth, the genetic code is the set of rules for interpretation and realization of genetic information. It is the most fundamental and the earliest manifestation of life being shared among all living organisms, as it establishes the information flow in biology. Biology as an analytical and informational science reach point to start to find routes to change and expand the repertoire beyond the canonical 20 (+2) amino acids of the genetic code, embracing a new chemical makeup of life.